Anti-GQ1b-negative Miller Fisher syndrome presented with one-sided horizontal gaze palsy - Akinci, Gülçin; Oztura, Ibrahim; Hiz-Kurul, Semra (The Turkish Journal of Pediatrics, 2010)
Miller Fisher syndrome classically presents with ophthalmoplegia, ataxia and areflexia. The syndrome may present rarely with atypical clinical features. Whether the central or peripheral nervous system is primarily involved remains controversial. Miller Fisher syndrome usually follows an infection, the most likely being Campylobacter jejuni. Mycoplasma pneumoniae has been reported rarely as the antecedent infectious agent in some patients. Herein, we report a 13-year-old girl with positive mycoplasma immunoglobulin (Ig)M and IgG serology who presented with one-sided horizontal gaze palsy, ataxia, areflexia, and bulbar palsy. Her cranial magnetic resonance imaging was normal and blood serum was negative for anti-GQ1b IgG antibodies.